Putting CYP2C19 genotyping to the test: utility of pharmacogenomic evaluation in a voriconazole-treated haematology cohort. (3rd January 2015) - Trubiano, J. A.; Crowe, A.; Worth, L. J.; Thursky, K. A.; Slavin, M. A.
Abstract: Objectives: The clinical utility of pharmacogenomic testing in haematology patients with invasive fungal disease (IFD) receiving azole therapy has not been defined. We report our experience with CYP2C19 testing in haematological patients requiring voriconazole therapy for IFD. Methods: As a single-centre pilot study, 19 consecutive patients with a haematological malignancy undergoing active chemotherapy with a possible, probable or proven IFD requiring voriconazole therapy underwent CYP2C19 testing from 2013 to 2014. Baseline patient demographics, concurrent medications, voriconazole levels and IFD history were captured. Results: The median voriconazole levels for intermediate metabolizer (IM) (CYP2C19*2 or 3/*1 or 17), extensive metabolizer (EM) (CYP2C19*1/*1) and heterozygote ultrarapid metabolizer (HUM)/ultrarapid metabolizer (UM) (UM, CYP2C19*17/*17; HUM, CYP2C19*1/*17) patients were 5.23, 3.3 and 1.25 mg/L, respectively. Time to therapeutic voriconazole levels was longest in the IM group, whilst voriconazole levels <1 mg/L were only seen in UM, HUM and EM phenotypes. The highest rates of clinical toxicity were seen in the IM group (3/5, 60%). Conclusions: Voriconazole exposure and toxicity was highest for IM and lowest for HUM/UM phenotypes. Time to therapeutic voriconazole level was longest in IM, whilst refractory subtherapeutic levels requiring CYP2C19 inhibition were only seen in the EM, HUM and UM phenotypes. CYP2C19 genotyping may predict those likely to have supratherapeutic or subtherapeutic levels and/or toxicity. Prospective evaluation of clinical pathways incorporating genotyping and voriconazole dose-titrating algorithms is required.